Multimodal cohesion through word formation: Sublexical cohesive ties in online illustrated step-by-step cooking recipes. (October 2021) - Sanchez-Stockhammer, Christina
Highlights: Most categories of lexical and grammatical cohesion have sublexical equivalents. There are several innovative sublexical types of cohesion, e.g. acronymic reference. Illustrated step-by-step cooking recipes show rich multimodal sublexical cohesion. As processed ingredients become more specific, this is expressed with compounding. Rich cohesion in step-by-step cooking recipes eases processing for non-expert cooks. Abstract: Cooking recipes represent a technical language register characterised by comparatively many complex word formations. However, recipes are also commonly read by non-expert users – an audience that benefits particularly from step-by-step instructions with photographs of the ingredients and the processes they enter. This contribution provides a discourse-analytical account of online step-by-step cooking recipes with illustrative photographs with regard to multimodal cohesive ties below the level of words. It explores how word formation processes, the morpho-semantic units they combine and the relations between these units can bring about cohesion. Providing a comprehensive discussion of word formation in the light of Halliday and Hasan's (1976) classical model, the paper explores the existence of sublexical equivalents for the categories of lexical cohesion, reference, substitution, ellipsis and conjunction, and discusses level-specific restrictions on cohesion (e.g. word formation type or headedness). The extended cohesive model is then applied to the analysis of authentic step-by-step cooking recipes in order to explain how e.g. the use of the compound banana bread in the title, the compound's initial constituent banana in the list of ingredients, a photograph of the finished, bread-like product, and a photograph of raw bananas as an unprocessed ingredient creates a rich multimodal sublexical cohesive network.